Role of Tourism in Local Development A Case of Sarangkot Hill-Top in Pokhara, Western Nepal - Bhusal, Narayan P. (The Third Pole: Journal of Geography Education, 2014)
Tourism management plan at the local level provides a framework for balanced development of a given area through the utilization of the existing tourism resources by the provision of tourism services that are required in order to attract the tourists from different parts of the world. Therefore, identifying and understanding of the natural, demographic and socio-cultural resource potential that enable a given area and its communities to shape tourism development according to local needs and within recognized environment and resource constrains. It is in this context the present paper is aimed to identify cultural and natural sites of tourism importance and problems and prospects of tourism for development in order to provide information on the basis of which can be undertaken sustainable actions for tourism development in Sarangkot VDC of Kaski district, Western Nepal. DOI: http://dx.doi.org/10.3126/ttp.v8i0.11507 The Third Pole: Journal of Geography Vol.8-10, pp. 9-19: 2010